Surface modification of ZIF‐90 with triptycene for enhanced interfacial interaction in mixed‐matrix membranes for gas separation. Issue 18 (25th August 2020) - Zhang, Qinnan; Luo, Shuangjiang; Weidman, Jennifer; Guo, Ruilan
Abstract: Zeolite imidazole framework (ZIF‐90) nanoparticles were chemically modified by grafting triptycene moieties. The modified nanoparticles were introduced into a triptycene‐based polyimide as fillers to generate mixed matrix membranes (MMMs) for gas separation. The incorporation of "hook‐like" triptycene moieties in both dispersed and continuous phases led to intimate contact between the two phases and thus defect‐free interfacial morphology, due to the supramolecular interlocking and π–π stacking interaction between triptycene units presented in both phases. The filler/polymer solution showed shear thickening behavior due to such strong interfacial interaction. The separation performance of the prepared composite membranes was investigated as a function of filler loading and particle surface grafting density. Pure‐gas permeation results showed that the gas permeabilities increased expectedly as the filler loading increased, with stable or improved selectivities. The reduced permeability relative to pristine polyimide film is likely due to the pore blockage of ZIF‐90 upon grafting triptycene moieties on the particle surface. Reducing the grafting density of triptycene moieties led to improved permeability and selectivity suggesting good tunability of this series of new composite membranes. Overall, modification of nanofiller with hierarchical triptycene moieties offers a fundamentally new avenue for creation of composite membranes with unique properties in gas separations. Abstract : A new series of mixed‐matrix membranes are developed via combining ZIF‐90 nanoparticles that are surface modified with hierarchical triptycene units with a triptycene‐based polyimide. Favorable interfacial interaction is achieved between polymer and filler phase via the strong supramolecular interlocking and π–π stacking of triptycene units in both phases. This new concept holds great promise in addressing the long‐standing unsolved interfacial issues in mixed‐matrix gas separation membranes, or more broadly, composite materials for various applications.